Իրանականի, իսլամականի և մոդեռնի սինթեզը որպես ազգային-մշակութային ինքնագիտակցության դրսևորում պարսից ժամանակակից արձակում - Գևորգյան, Գառնիկ (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
One of the characteristics of the modern Persian prose is the synthesis of centuries-old national literary traditions with new directions in world literature. In the formation of "the subjective prose" in the 20th century Persian literature, S. Hedayat's novel "Buf-e kur" (Blind owl, 1937) has been of fundamental importance. With this, Iranian literature enters the stage of psychoanalysis, observing the vital phenomena of man and the world around him with a new philosophy. The works with such content published in 1950-1960s. turned subjective prose into a separate direction, creating fertile ground for the emergence of the modernist second direction. The most improved version of the subjective prose was formed in the 60-70s with the active use of the method of "stream of consciousness", one of the pioneers of which is H. Golshiri's novel "Shazde Ehtejab" (Prince Ehtejab).
Keywords: Պատմություն